Carbon nanotube assembly at near-industrial natural-fiber spinning rates. (May 2015) - Alvarez, Noe T.; Miller, Peter; Haase, Mark; Kienzle, Nicholas; Zhang, Lu; Schulz, Mark J.; Shanov, Vesselin
Abstract: A large number of carbon nanotube (CNT) applications require that CNTs be assembled into fibers and films at speeds viable for industrial production processes. Most of the state-of-art CNT thread formation techniques of CNT fiber production in meters per second (m/s) are still an order of magnitude lower than typical industrial processes. Here, we report a modified dry spinning process with improved drawing rates, where catalyst-free CNT films can be drawn at 15.93 m/s, an order of magnitude higher than most similar dry spinning processes reported in literature. We achieved this speed by using spinnable CNT arrays that are completely detached from the substrate and the corresponding catalyst nanoparticles. The detached drawable CNT arrays are free-standing and they can be transferred onto other flat substrates. This allows the formation of CNT threads with higher diameter uniformity; also the Si substrates can be re-used. Additionally, we successfully attached single-layer CNT ribbons from different batches in order to produce arbitrarily long CNT fibers and threads.